Αlpha-lipoic acid and l-arginine on in vitro production of ovine embryos - Freitas, Beatriz Cavalcanti de (2023)
The objective of this study was to evaluate the effect of α-lipoic acid on in vitro maturation and of l-arginine on in vitro fertilization of oocytes for in vitro production of sheep embryos. Thus, the ovaries were collected at a local slaughterhouse and the oocytes collected by the method of follicular aspiration with a vacuum pump were divided equally into five maturation groups: CON, without addition of antioxidant; CIS group, with cysteamine as an antioxidant source; and the groups ALA5, ALA10 and ALA20, containing concentrations of 5.0, 10.0 and 20.0 µM of ALA. After 24h of maturation, the oocytes were evaluated concerning occurrence and degrees of expansion of the cumulus cells. The oocytes of the best IVM group were destinated for in vitro fertilization (IVF). The selected and capacitated sperm were included in five groups: CON, without addition of capacitator agent; HEP group, with heparin as a capacitator source; and ARG5, ARG10 and ARG20 groups, where IVF occurred in the same HEP medium, replacing heparin with 5 mM, 10 mM and 20 mM L-arginine, respectively. The results were expressed as a percentage and the variables of cumulus cell expansion and number of cleaved structures were compared using the chi-square test in Epi Info software (Epi Info 7.2.5, Atlanta, GA, USA, 2021). Results were considered significant when P < 0.05. Regarding the expansion of cumulus cells all groups showed 100% expansion, on the total expansion category of COCs it was observed that ALA5 and ALA20 groups did not present the same proportion of COCs with total expansion as CIS group. After in vitro fertilization (IVF), there were no statistical differences in relation to the cleaved structures between CON, HEP, ARG5 and ARG10 groups. However, it was also observed that the use of 20.0 mM of L-arginine reduced the percentage of cleaved structures when compared to the ARG10 group (P<0.05).